2012
DOI: 10.2214/ajr.11.6984
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Percutaneous Catheter Drainage of Acute Infectious Necrotizing Pancreatitis: Assessment of Effectiveness and Safety

Abstract: Percutaneous catheter drainage is a safe and effective technique to treat acute infectious necrotizing pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 32 publications
3
55
0
Order By: Relevance
“…The etiology of infected pancreatitis necrosis was reported in 9 studies [8,16,17,25,27,28,[33][34][35], in which the most common cause was biliary tract disease. APACHE II scores and CT severity index scores were used in the 10 studies [8,16,17,28,29,31,[33][34][35][36]; 0.195 (55.3 %) of 352 patients had organ failure before PCD in 9 studies (including single and multiple organ failure) [8,17,29,30,[32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The etiology of infected pancreatitis necrosis was reported in 9 studies [8,16,17,25,27,28,[33][34][35], in which the most common cause was biliary tract disease. APACHE II scores and CT severity index scores were used in the 10 studies [8,16,17,28,29,31,[33][34][35][36]; 0.195 (55.3 %) of 352 patients had organ failure before PCD in 9 studies (including single and multiple organ failure) [8,17,29,30,[32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported the mean length of hospital stay [16,[27][28][29][31][32][33], which ranged from 3 to 241 days. Eight studies reported the mean length of initial treatment with PCD after hospital admission [8,16,17,25,28,29,32,35]. The success rate of PCD, defined as the recovery of patients without additional surgical intervention, was 56.2 % (324 of 577 patients).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations